UVEITIS: OCULAR MANIFESTATIONS OF RHEUMATIC DISEASES AND MULTIDISCIPLINARY APPROACHES. - Prado , Karollyne Francisco; Couto, Laís Cristina; Moreira , Joyce Emanuelle; Bontempo, André Sardinha; Santos , João Luiz Duarte (Brazilian Journal of Implantology and Health Sciences, 2024)
Uveitis, an ocular inflammation that affects the uvea, is often associated with rheumatic diseases such as rheumatoid arthritis and systemic lupus erythematosus. This intersection between ophthalmology and rheumatology demands a multidisciplinary approach for adequate diagnosis and treatment. Understanding the ocular manifestations of these rheumatic diseases is crucial to prevent permanent damage to vision and improve patients’ quality of life. Objective: This study aims to conduct a systematic review of the literature to analyze the ocular manifestations of rheumatic diseases, with a focus on uveitis, and explore the multidisciplinary approaches used for its management. Methodology: Using the PRISMA checklist, we searched the PubMed, Scielo and Web of Science databases for articles published in the last 10 years. The descriptors used were "uveitis", "rheumatic diseases", "ocular manifestations", "multidisciplinary approach" and "treatment". The inclusion criteria were original studies and reviews that addressed the relationship between uveitis and rheumatic diseases, while the exclusion criteria were duplicate studies, unrelated to the topic and with inadequate methodology. Results: The results highlighted the prevalence of uveitis in several rheumatic diseases, the different types of associated ocular inflammation and the multidisciplinary therapeutic strategies adopted. Effective treatments have been identified to control inflammation and preserve vision, emphasizing the importance of collaboration between ophthalmologists and rheumatologists. Conclusion: A multidisciplinary approach is fundamental in the management of uveitis associated with rheumatic diseases, allowing early diagnosis, effective treatment and prevention of complications. This review highlights the importance of working together between medical specialties to improve clinical outcomes and quality of life for patients affected by this condition.